THE IMPACT OF USING ENGLISH SUBTITLED MOVIES IN STUDENTS’ SPEAKING ABILITY - Muhamad Samsul Fauji; Mukminatus Zuhriyah (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study develops a different way to teach language, namely by using subtitled films as a medium. Here the researcher uses cartoons and English subtitles. The purpose of this study was to determine the speaking ability of the experimental and control groups, as well as to determine the significant effect of using English subtitled films on the speaking ability of class XI students at SMA Negeri Ngoro for the academic year 2020/2021. The design of this study was a quasi-experimental with nonrandomized control group design, pretest-posttest design. There is a significant effect of using film subtitles as a medium in teaching speaking. Teaching speaking using film subtitles as a medium is more effective than teaching speaking using film. So, the researcher can conclude that English subtitled films have an impact on students' speaking ability.